Understanding and changing your management style assessments and tools for self-development - Benfari, Robert (San Francisco Jossey-Bass, 2013)
An update of the classic book that reveals the 6 keys to successful management In this new edition of his best-selling book, Robert Benfari explains that the best mangers are not born that way but share a mix of characteristics that can be analyzed, understood, and most importantly changed. He identifies the six characteristics of successful managers (Psychological Type; Needs/Motivation; Use of Power; Conflict Style; Our Basic Values; and Our Reaction to Stress) and uses these building blocks to show how anyone can use personality-specific strategies for resolving conflicts, solving problems, managing stress, handling difficult situations at work, and positively influencing others.
Includes bibliographical references (pages 331-336) and index.
Keywords: Executive ability